THE CONTRIBUTION OF ARCHAEOLOGY DEPARTMENT GRADUATES TO THE STUDY OF CENTRAL ASIAN CULTURAL HISTORY - Сагдуллаев А. С. (TARIXIY TADQIQOTLAR, 2025)
This article examines certain aspects of the formation and development of the Department of Archaeology of Central Asia – the first specialized school of archaeology in the region – as well as the contributions of its graduates to the study of archaeological sites and the cultural history of Central Asia.